2020
DOI: 10.21873/anticanres.14117
|View full text |Cite
|
Sign up to set email alerts
|

Performance Status Is Associated With Survival in Elderly Patients Irradiated for Cerebral Metastases from Prostate Cancer

Abstract: Background/Aim: Treatment of elderly patients with cancer has increasing importance. Since many of these patients may not tolerate standard treatments, they might benefit from personalized approaches. This study was performed to identify characteristics that allow estimation of survival in elderly patients with prostate cancer with cerebral metastases. Patients and Methods: Data of 21 elderly patients (≥65 years) receiving whole-brain radiotherapy (WBRT) for cerebral metastases from prostate cancer were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Further factors that were associated with survival were performance status, RPA class, the use of cranial radiotherapy in cohorts including untreated patients and the time from prostate cancer diagnosis to diagnosis of brain metastases or WBRT (3,18,19). Better performance status and lower RPA class were also associated with improved survival in this analysis.…”
Section: Methodsmentioning
confidence: 74%
“…Further factors that were associated with survival were performance status, RPA class, the use of cranial radiotherapy in cohorts including untreated patients and the time from prostate cancer diagnosis to diagnosis of brain metastases or WBRT (3,18,19). Better performance status and lower RPA class were also associated with improved survival in this analysis.…”
Section: Methodsmentioning
confidence: 74%
“…The manual reference search conducted for each of the 23 selected articles resulted in the selection of an additional four articles. Ultimately, a total of 27 articles were included in this analysis, spanning the period from 1976 to 2021 [ 4 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, the locations of synchronous metastases were not reported by specific location but instead reported as visceral metastases. Each of those particular studies reported high rates of concurrent visceral metastases ranging from 59% to 81% [ 12 , 37 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that patients with poor general condition have short survival time and are independent prognostic risk factors for advanced NSCLC 14 Behavior state score (performance score, PS, or Karnofsky Performance Score, KPS) are widely used to assess general condition of cancer patients. Nguyen T et al 15 showed in a study of 21 elderly (>65 years old) patients with advanced cancer that behavioral performance is an important index affecting the survival rate of patients. In our study, univariate and multivariate analyses showed that PS score was related to survival time.…”
Section: Discussionmentioning
confidence: 99%